THE ROLE OF LONELINESS AS A PREDICTOR OF INTERNET ADDICTION WITH A MEDIATING EFFECT OF SELF ESTEEM AND MODERATING EFFECT OF RESILIENCE AMONG INTERNATIONAL STUDENTS IN CHINA - Saeed, Maaza (International Journal of Psychosocial Rehabilitation, 2020)
Internet addiction has emerged as a major concern of the current decade and inner psychological factors has found to be the protective or enhancing factor in internet addiction. The aim of the present study was to inquire into the mediating role of self-esteem in the association among loneliness and IA. Secondly, to investigate the moderating role of the resilience in the indirect relationship between loneliness and internet addiction. Participants was 436 (mean age = 23.81 years, SD = 1.91) and they completed the survey questionnaire comprised of loneliness, self-esteem, internet addiction and resilience. The correlation analyses revealed that loneliness was significantly positively, and resilience was negatively associated with IA of the international students. Self-esteem mediated the link between loneliness and internet addiction. However moderated mediation advised resilience only moderated the path between self-esteem and IA, Though resilience did not moderate the relation between loneliness and self esteem’s first-stage moderation. Results suggest high level of self-esteem and resilience can be a preventive component against IA in international students. Overall, these findings highlighted suggestions for internet addiction among international students.